Zearalenone and nanozeolite improve Arugula (Eruca sativa) drought tolerance by enhancing photosynthesis and water relations - Najmeh Zeinalipour; Fatemeh Galehdari; Safoora Saadati; Mohammad Javad Arvin; Mehdi Sarcheshmehpour (Scientific Reports)
Abstract This study investigated the effects of zearalenone (ZEN) and nanozeolite (NZ) on arugula (Eruca sativa) under deficit irrigation in a controlled greenhouse environment. Using a split-plot design, two irrigation levels (100% and 70% field capacity: FC) were applied, along with ZEN (60 and 120 ppb), NZ (1.5 and 3 ppm), and a control with no additives. Both ZEN and NZ significantly enhanced arugula’s drought tolerance by improving photosynthetic efficiency, water use efficiency (WUE), plant water status, growth, proline accumulation, and antioxidant activity. Notably, NZ at 3 ppm was most effective, increasing net photosynthesis by 2.84-fold, WUE by 2-fold, and reducing transpiration by 4.33-fold and electrolyte leakage by 1.19-fold under 70% FC compared to the control. NZ at this concentration also improved chlorophyll fluorescence, raising Fv/Fm by 52% (up to 0.8) and lowering non-photochemical quenching (NPQ) to 0.33, indicating enhanced photosystem II efficiency and reduced photoprotective demand. ZEN at 120 ppb also improved drought resilience by increasing Fv/Fm, reducing NPQ, enhancing chlorophyll content, maintaining higher relative water content and osmotic potential, increasing leaf area and shoot fresh weight, and boosting proline accumulation, though its effects were generally less pronounced than those of NZ. These findings suggest ZEN and NZ as promising amendments for improving arugula’s resilience to water stress in controlled environments, with potential applications in water-scarce agricultural systems pending field validation.